Topology Optimization and Advanced Manufacturing as a Means for the Design of Sustainable Building Components. (2016) - Donofrio, Mark
Abstract: This paper presents research exploring the potential of topology optimization as a means for the design of sustainable building components. Topology optimization is a mathematical, gradient-based design procedure that can be used to determine the distribution of required material within a design domain based upon defined loads and boundary conditions while meeting a prescribed target objective, such as minimizing deflection. The concept of topology optimization has been utilized by the automotive and aerospace industry for almost thirty years now, since its early development, where problems associated with solutions meant to satisfy maximum stiffness with minimum weight are of the utmost importance. The recent saturation of digital design tools and techniques within the architecture industry have led more and more architects to seek computationally driven, data-centric, methodologies to assist in the design process. Topology optimization is well suited as a methodology to assist in the development of form that is rooted in sound structural logic while striving for material efficiency. This paper presents case studies of recent architectural projects that utilize topology optimization for projects ranging from long-span roof structures to high-rise buildings. Advances in advanced manufacturing are also examined as a means of more easily realizing sustainable building systems through this use of topology optimization.